The Impact of Work Ethic and Transformational Leadership on Employee Performance Mediated by Work Motivation at Company XYZ - Ardelia Putri Tamara; Muhammad Halim Maimun (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study aims to analyze the effect of work ethic and transformational leadership on employee performance, with work motivation as a mediating variable at Company XYZ. The study is motivated by the importance of managing behavioral factors and leadership practices to enhance employee performance in a dynamic organizational environment. A quantitative approach was employed through a survey. Primary data were collected through closed-ended questionnaires distributed to 120 permanent employees of Company XYZ, selected using purposive sampling. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results indicate that work ethic has a positive and significant effect on employee performance and work motivation. In contrast, transformational leadership has no significant direct effect on employee performance or work motivation. Work motivation has a positive and significant effect on employee performance. It mediates the relationship between work ethic and employee performance, but not the effect of transformational leadership. These findings suggest that improving employee performance is more effectively achieved by strengthening work ethic and enhancing work motivation than by relying on the direct or indirect influence of transformational leadership. The practical implications of this study highlight the importance of human resource management strategies that cultivate a strong work ethic and internal motivation to achieve sustainable performance improvements.